Insights into the Andean genera Bridgesia and Guindilia (Sapindaceae): an integrated approach. Issue 6 (1st November 2016) - Urdampilleta, Juan D.; Coulleri, Juan P.; Ferrucci, MarÍa S.
Abstract : Sapindaceae s.l. is a moderately large family of trees, shrubs and lianas. The genera Bridgesia and Guindilia belong to the Thouinieae tribe; however, its circumscription to this tribe is in doubt. This work presents a comparative analysis of pollen morphology between species of both genera. They share the basic spherical tricolporate pollen type for the family, but the features studied do not characterize any of them. In addition, the work intends to characterize the karyotype and genome size evolution of both genera, and elucidate the phylogenetic relationships within the family through maximum likelihood and Bayesian analyses of the ITS, trn L and trn L-F sequences. Our results show two different patterns regarding karyotype data: Bridgesia presents 2n = 2x = 28, with metacentric and submetacentric chromosomes; the basic number of the genus, x = 14, is in agreement with the 25% of the chromosome numbers recorded in Sapindaceae. The genus Guindilia exhibits a basic number x = 10; of the three species G. cristata and G. trinervis present metacentric, submetacentric and subtelocentric chromosomes, whereas G. dissecta shows only metacentric and subtelocentric ones. In addition, G. cristata is a polyploid species, with DNA content exactly three-fold that of the diploid species, suggesting a recent event of polyploidization in this species. The infra-familial phylogenetic relationship and circumscription of both genera analysed here evidence that Bridgesia belongs to Paullinia group. The fact that Guindilia is grouped in a different clade encouraged us to propose a new informal tribal group, Guindilia group, in the current infrafamilial arrangement of Sapindaceae.